How English Works : A Grammar Practice Book - Swan, Michael (New York Oxford University Press, 1998)
Combining rich illustrations and authentic exercises, How English Works makes the learning and practising of grammar both a pleasure and a challenge. The author's imaginative and wholly original approach to the presentation and organisation of their text offers students a lively, purposeful package to give them a confident command of English forms and their uses. Designed for students working on their own, but also ideal for use in class, How English Works covers all the key elements in the standard EFL grammar syllabus, and many other topics which are often ignored. -- Publisher description
Including Index And Color Illustration
Keywords: English language--Grammar -- English language -- English language--Usage